The amazon várzea The decade past and the decade ahead - Pinedo-Vasquez, Miguel; Rufino, Mauro L.; Padoch, Christine; Brondizio, Eduardo S.; SpringerLink (Online service). (Dordrecht Springer Netherlands Imprint: Springer, 2011)
This book takes a multi-disciplinary and critical look at what has changed over the last ten years in one of the world's most important and dynamic ecosystems, the Amazon floodplain or várzea. It also looks forward, assessing the trends that will determine the fate of environments and people of the várzea over the next ten years and providing crucial information that is needed to formulate strategies for confronting these looming realities. The volume includes the latest research and analysis from a broad range of scientists who know the várzea best. It is dedicated to the memory of José Márcio Ayres, one of Brazil's greatest natural scientists and a pioneer in várzea research and conservation.
Preface I: The Várzea: The Decade Past -- Preface II: The Várzea: The Decade Past and the Decade Ahead: An Introduction -- List of Contributors -- List of Figures -- List of Tables -- PART I -- PART II -- PART III -- PART IV -- PART V -- PART VI -- Index.
Electronic reproduction.
Keywords: Floodplain ecology--Amazon River Valley--Congresses.; Floodplain forest ecology--Amazon River Region--Congresses.; Ecosystem management--Amazon River Valley--Congresses.; Human ecology--Amazon River Region--Congresses.; Environmental policy--Amazon River Region--Congresses.; Conservation of natural resources--Amazon River Valley--Congresses.; Amazon River Valley--Environmental conditions--Congresses.; Electronic books